The differences in medium of instruction for the lower primary phase in teacher education and schools in Namibia, with reference to the Kavango educational region, are a barrier to effective teaching and learning - Hausiku, Scholastika Mbava (Centre for Applied Language and Literacy Studies and Services in Africa, 2015)
The study aims to investigate whether the difference in the language of teaching in teacher education and the language of teaching in the lower primary phase is a barrier for effective teaching and learning in the targeted institutions. Furthermore, would additional focus on mother tongue education in teacher education benefit educational achievement in the Kavango educational region specifically and in Namibia as a whole?